Cardiac arrest and pulmonary hypertension in scurvy: a case report. (December 2018) - Dean, Terry; Kaushik, Neeru; Williams, Sharron; Zinter, Matthew; Kim, Paul
We report a case of a six-year-old boy who presented after a cardiac arrest, likely due to a pulmonary hypertensive crisis in the setting of vitamin C deficiency. After initially presenting with subacute multifocal bone lesions of unknown etiology, he experienced a pulseless electrical activity cardiac arrest while undergoing a diagnostic procedure under sedation. During his post-arrest convalescence, he developed persistent tachycardia and peripheral edema. An echocardiogram revealed findings consistent with significant pulmonary arterial hypertension, which was found to be responsive to inhaled nitric oxide. Laboratory investigation revealed undetectable levels of vitamin C, resulting in disclosure of a history of severe restrictive eating behavior. With ascorbate supplementation, the patient's pulmonary vasodilators were weaned and discontinued. Given his complete recovery, we suspect that the cardiac arrest and pulmonary hypertension were the consequence of a rare, but reversible, complication of scurvy.